Heterogeneous Stem Cells in Skin Homeostatis and Wound Repair - Anna Meilana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2015)
BACKGROUND: The skin protects mammals from insults, infection and dehydration and enables thermoregulation and sensory perception. Various skin-resident cells carry out these diverse functions. Constant turnover of cells and healing upon injury necessitate multiple reservoirs of stem cells. The skin is a complex organ harboring several distinct populations of stem cells and a rich array of cell types. Advances in genetic and imaging tools have brought new findings about the lineage relationships between skin stem cells and their progeny. Such knowledge may offer novel avenues for therapeutics and regenerative medicine.CONTENT: In the past years, our view of the mechanisms that govern skin homeostasis and regeneration have markedly changed. New populations of stem cells have been identified that behave spatio-temporally differently in healthy tissues and in situations of damage, indicating that a great level of stem cell heterogeneity is present in the skin. There are believed to be distinct populations of stem cells in different locations. The lineages that they feed are normally constrained by signals from their local environment, but they can give rise to all epidermal lineages in response to appropriate stimuli. Given the richness of structures such as blood vessels, subcutaneous fat, innervation and the accumulation of fibroblasts under the upper parts of the rete ridges (in the case of human skin), it is reasonable to speculate that the microenvironment might be essential for interfollicular epidermal homeostasis. The bloodstream is probably the main source of long-range signals reaching the skin, and cues provided by the vascular niche might be essential for skin homeostasis.SUMMARY: A key function of the interfollicular epidermis is to act as a protective interface between the body and the external environment, and it contains several architectural elements that enable it to fulfill this function. All elements of the epidermis play active roles in regulating skin function, which might not have been anticipated from their role in maintaining skin integrity. Skin cell research benefits from the integration of complementary technologies and disciplines. How skin function is regulated and how it may be possible to intervene to treat a variety of skin conditions. Ultimately also impairing the maintenance of self-renewing satellite cells. Therefore, only anti-aging strategies taking both factors, the stem cell niche and the stem cells per se, into consideration may ultimately be successful.KEYWORDS: epidermis, hair follicle, fibroblast, skin stem cells, homeostasis, regeneration